Criminal Responsibility for Children - Crime of Inducing Victims to Commit Sexual Intercourse (Study Decision Number 40/Pid.Sus-Anak/2023/PN.Tjk) - Ikhsan, Khafifa Adhelia Putri; Jainah, Zainab Ompu (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Sexual harassment is behavior or attention of a sexual nature that is unwelcome and undesirable and has the effect of disturbing the recipient of the harassment. Sexual harassment includes, but is not limited to: sexual payment for wanting something, coercion to carry out sexual activities, derogatory statements about sexual orientation or sexuality, requests to perform sexual acts that the Child likes, speech or behavior that has a sexual connotation; all can be classified as sexual harassment. This action can be conveyed directly or implicitly. The problem in this research is what are the factors that cause children to commit the crime of persuading victims to commit sexual intercourse based on Decision Number 40/Pid.Sus-Anak/2023/PN. Tjk? and What is the criminal responsibility for children committing the crime of persuading the victim to commit sexual intercourse based on Decision Number 40/Pid.Sus-Anak/2023/PN. Tjk? The research method used in this thesis research is a normative juridical approach and an empirical approach. Secondary data is data obtained through library research, such as literature books and scientific works related to research problems. Secondary data consists of 3 (three) legal materials, namely, primary, secondary and tertiary legal materials. Prime data is data obtained from research results in the field directly on the research object (field research) which is carried out by means of direct observation and interviews regarding the object in writing this thesis. Based on the research results obtained, it can be concluded that the factors causing a father to commit a criminal act of deception and persuading a child to have sexual intercourse are due to several factors such as internal factors in the form of the defendant's lack of understanding of religion. The defendant's mental condition was also a contributing factor, as well as the defendant's sexual disorder such as pedophilia, where the defendant preferred small children to someone his own age. Apart from internal factors, there are external factors that also influence the defendant in committing the crime, such as environmental conditions and the condition of the defendant's place of residence which support the commission of the crime, being unable to give vent to his sexual desires because his wife is not at home, the defendant's low education, and the media. and technological advances were also part of the external factors that caused the defendant to commit this act. Criminal Responsibility for Children Committing the Crime of Inducing the Victim to Commit Sexual Intercourse Based on Decision Number 40/Pid.Sus-Anak/2023/PN. Tjk with the punishment of institutional development for 2 (two) years at the Bandar Lampung Class II Special Child Development Institution (LPKA) in Masgar Pesawaran and job training for 3 (three) months at the Social Welfare Organization (LPKS) in Hurun Pesawaran Village. The suggestions that can be conveyed in this writing are suggestions for the community, especially parents, to provide sex education in the family environment in order to minimize the occurrence of free sex among the next generation of the nation as it is known that free sex can cause dangerous sexually transmitted diseases, otherwise done correctly and precisely. and Suggestions for the Government. There needs to be a law that emphasizes the protection of women and children and socializes it within the community so that people know the consequences of the act of rape.